Ceramic-polymer composites for electronic packaging - Chan, Chin Kiat (Nanyang Technological University, 2021)
This project aims to develop a high thermal conductive material capable of being used for electronic packaging to combat the challenges such as overheating in electronic devices resulting from limits of miniaturization and increase in packing density of transistors. The highly isotropic thermal properties of hexagonal Boron Nitride (hBN) show a promise as a candidate to pave the way to high performance and reliable electronics. In this report, both fabrication and characterization of magnetically aligned magnetic hexagonal Boron Nitride (mhBN) will be discussed, along with the effects of sintering at various temperature, and the efforts to infiltrate the samples with an epoxy polymer matrix.